Herbal Drugs, Diet and Lifestyle Changes for Liver Diseases- A Review - S. Sivakrishnan (Journal of Global Pharma Technology, 2019)
The liver is an important part of human digestive system. The organ’s function include food metabolism, energy storage, waste removal, detoxicification, immune system support and production of chemicals. There are several things damage the liver such as toxic substances, viruses, medications, genetic diseases and alcohol. Some of the herbal drugs and its extracts showed a good potentials for use in liver diseases.  Therefore, the present work constitutes a review of the literature on plant extracts and chemically defined molecules of natural origin with hepatoprotective activity. In addition diet and lifestyle changes can help to improve the conditions of hepatotoxicity.